Assessment of the acid mine drainage potential of waste rocks at the Ak-Sug porphyry Cu–Mo deposit; Journal of Geochemical Exploration; Vol. 157 - Abrosimova N. A. Nataljya Aleksandrovna; Gaskova O. L. Olga Lukinichna; Loshkareva A. A. Aleksandra Aleksandrovna; Edelev A. V. Aleksey Viktorovich; Bortnikova S. V. Svetlana Borisovna (2015, 2015)
Title screen